Postpartum hemoptysis as presenting sign of longstanding vasculitis. (November 2018) - Berman, D.J.; Knibbs, N.; Friedman, L.; Rocco, M.
Highlights: Medium vessel vasculitis is a rare diagnosis. Pregnancy outcomes in patients with vasculitis are poor. Autoimmune diseases often flare in the postpartum period. Therapy for vasculitis often involves immunosuppression. A multidisciplinary approach is helpful to manage these patients. Abstract: We present the case of a 26-year-old postpartum patient who presented with an episode of desaturation and hemoptysis on postpartum day three after an uncomplicated spontaneous vaginal delivery. The patient came to our attention in the postpartum area after she experienced massive hemoptysis and we were called by the obstetric team. The patient was subsequently intubated, mechanically ventilated, and underwent bronchoscopy, demonstrating diffuse alveolar hemorrhage. She was brought to the intensive care unit, placed on high-dose steroids and plasmapheresis was initiated. Her intensive care unit course was complicated by acute respiratory distress syndrome, acute kidney injury and a pulmonary embolism, but she recovered well and was discharged on postpartum day 23. This report describes a rare case of medium vessel vasculitis diagnosed in the peripartum period, and describes the diagnostic dilemmas underlying making a rare diagnosis, and the difficulties initiating appropriate therapy in a postpartum patient.